BASIC PRINCIPLES OF COMPARATIVE LINGUISTICS - Zilola Abduraxmonova; Safarova Dildora Alisher kizi (TADQIQOTLAR.UZ, 2023)
This article highlights several ways to learn English effectively and some of the modern learning technologies in language learning as well.